2016
DOI: 10.1016/j.gore.2016.10.003
|View full text |Cite
|
Sign up to set email alerts
|

Papillary squamous cell carcinoma of the cervix: Two cases and a review of the literature

Abstract: ObjectivePapillary squamous cell carcinoma of the cervix (PSCC) is a rare and distinct form of cervical carcinoma. Detecting stromal invasion on biopsy is difficult due to the papillary growth of the tumor. Here we present two cases that highlight the diagnostic and clinical challenges of PSCC.Case 1A 50-year-old woman found to have carcinoma on a routine pap-smear. The patient was diagnosed with PSCC on colposcopic biopsy and underwent a radical hysterectomy, bilateral salpingo-oophorectomy and pelvic lymph n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
16
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(17 citation statements)
references
References 10 publications
(38 reference statements)
1
16
0
Order By: Relevance
“…In conclusion, PSTCC has been reported to represent 1.6% of all cancer cervix [5] . It is a very distinct histologic variant associated with an aggressive biological behavior.…”
Section: Discussionmentioning
confidence: 79%
See 2 more Smart Citations
“…In conclusion, PSTCC has been reported to represent 1.6% of all cancer cervix [5] . It is a very distinct histologic variant associated with an aggressive biological behavior.…”
Section: Discussionmentioning
confidence: 79%
“…Original data suggested that PSCC behaves clinically like traditional squamous cell carcinoma. Recently the disease has been suggested to be less aggressive than typical SCC [5] . Koenig et al Studied 32 cases of PSTCC cervix.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…8 However, due to its distinct clinical behavior it should be distinguished from other TCC and other papillary lesions of the cervix, including condyloma, squamous papilloma, verrucous carcinoma, and cervical intraepithelial neoplasia grade 3 with papillary configuration. [9][10][11][12] PSTCC grossly has a distinguishing surface papillary growth pattern and can be deeply invading. Histologically, it is characterized by sheets of atypical basaloid cells, often non-keratinizing, showing moderate to severe nuclear atypia, and supported by fibrovascular cores.…”
Section: Resultsmentioning
confidence: 99%
“…Cervical PSCC is considered to be less aggressive than classic squamous cell carcinoma. However, some case reports have demonstrated the complex behavior of the disease. As a result, the pathologic examination of colposcopy‐guided biopsy samples does not always reveal the presence of stromal invasion.…”
Section: Discussionmentioning
confidence: 99%